Tracking the activity of supermassive black holes and the habitats of their hosts - Krishnan, Charutha (2020)
In this thesis, we explore the connections between active galactic nuclei (AGN) and the environments of their host galaxies across cosmic time, as viewed using three complementary angles. Much of this thesis is based on recently available, state-of- the-art data. Our galaxy catalogues comprise deep, multi-wavelength data provided by the UKIDSS Ultra Deep Survey (UDS) and Cosmic Evolution Survey (COSMOS). The UDS field contains a dense structure at z ∼ 1.6 with additional narrow-band imaging tailored to its redshift, allowing for the selection of protocluster members using precise photometric redshifts (Hatch et al. 2016). Both the UDS and COSMOS have coverage from X-ray telescopes such as Chandra and XMM-Newton, enabling the clean selection of AGN. This thesis also makes use of galaxy classifications (such as star-forming, passive, and post-starburst) based on principal component analysis (PCA) of broad-band photometry.